2018
DOI: 10.1212/wnl.0000000000005351
|View full text |Cite
|
Sign up to set email alerts
|

Aminophylline for treatment of postdural puncture headache

Abstract: This study provides Class I evidence that for people with PDPH, IV aminophylline reduces headache severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 22 publications
2
16
1
Order By: Relevance
“…Some studies suggested that 250 mg of aminophylline can be effective in the treatment of PDPH without significant side-effects and it can be used in parturients without affecting lactation. 6,21 In this current study, no adverse reactions were observed in all pregnant women and infants. Therefore, the dosage of aminophylline used in the study was safe.…”
Section: Discussionsupporting
confidence: 43%
See 1 more Smart Citation
“…Some studies suggested that 250 mg of aminophylline can be effective in the treatment of PDPH without significant side-effects and it can be used in parturients without affecting lactation. 6,21 In this current study, no adverse reactions were observed in all pregnant women and infants. Therefore, the dosage of aminophylline used in the study was safe.…”
Section: Discussionsupporting
confidence: 43%
“…4,5 Recently, it was shown that oral or intravenous administration of theophylline or aminophylline can be effective in the treatment of PDPH, and that early treatment with aminophylline was more effective. 6 However, there have been no reports on the prevention and treatment of PDPH in patients after caesarean section. Therefore, the objective of this current study was to investigate the effect of aminophylline on the occurrence of PDPH in patients undergoing caesarean section under CSEA and to provide reference information for the clinical prevention of PDPH.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic measures with aminophylline and caffeine have been proven effective. 62 Notably, both substances elevate breathing frequency, which, considering it the main driving force, could result in more profound CSF being moved upward into the cranial vault.…”
Section: Spontaneous Intracranial Hypotension and Rhinoliquorrheamentioning
confidence: 99%
“…This therapeutic effect was already evident at the 30-minute time point and persisted for 2 days. There was no significant difference in the incidence of adverse events (18) .…”
Section: In Addition Chuanjie Et Al (2018)mentioning
confidence: 76%